A survey of students’ perception on exploiting popular songs in motivating lower secondary school students in learning English / Muhamad Amirul Asraf Mohd Shariff - Mohd Shariff, Muhamad Amirul Asraf (2011)
This study aims at the students’ perception towards the exploitation of popular songs in motivating lower secondary school students in learning English language. The process of teaching and learning should be made enjoyable, meaningful and most of all, purposeful. This is the most important step of gaining the interest of students. In the case of teaching English language, teachers often do not realize the importance of the aspect of listening and thus take it for granted. Activities based on listening, ranging from listening to verbal instructions from the teacher to the listening from text reading of peers, are not challenging and authentic enough. 50 students of Sekolah Menengah Kebangsaan Tun Tijah, Melaka, were chosen as respondents, in which they were required to complete a questionnaire adapted from Chung-Chen & Ching Chen (2009). Findings gathered from the questionnaire indicate that the students perceive the method positively.